A multi-country trend indicator for euro area inflation: computation and properties - Elena Angelini; Jérôme Henry; Ricardo Mestre (European Central Bank (ECB), 2001)
This paper applies the 'diffusion indices' approach proposed by Stock and Watson [1998] to the euro area. Following their methodology a set of factors are extracted from a balanced and unbalanced panel dataset comprising nominal variables for 11 countries of the euro area. The estimated factors appear to be fairly stable over time. It is also shown that the first factor is cointegrated with area wide HICP and private consumption deflator supporting the idea that it represents 'a common trend of inflation' for the euro area. The other factors, which are stationary instead, seem to capture dispersion of inflation across countries. There is moreover evidence of unilateral causality from the first factor with respect to HICP, suggesting that this factor could be valuably employed in forecasting euro area inflation
Keywords: E52; E58; 330